Improving the Efficiency of Water Management System in Biomass Power Plant Using Cyber-Physical Cloud Computing - Pranai Kungwalrut; Viriya Kongratana; Thanit Trisuwannawat; Vittaya Tipsuwanporn; Arjin Numsomran (My University, 2018)
Optimized water management strategies are among the most crucial concerns in a biomass power plant.Especially during the times of water scarcity, an improper water supply planning and operation result in a detrimental power generation or shut down processes.This paper aims to propose the cyber-physical cloud computing (CPCC), a mechanism of analysis and control physical process using cloud-based framework, in order to improve the efficiency of water management system in a biomass power plant.In this study, a 9.9 MW biomass power plant is implemented to investigate the performance of CPCC.The architecture of the proposed system consists of three physical tiers.The first tier is a tier of physical devices included with pressure, flow, pH sensors, water pumps and valves that are responsible for detecting the physical data and interacting with the water production process.The second tier is an edge computing device which functions as a controller, embedded server, data storage, gateway and switch to manage all operational tasks in an intranet area.The third tier is a cloud computing system which enables big data applications such as online monitoring and visualization of process operation, adaptive filtration fouling control, consuming water and total water cost analysis.The results validate the effectiveness of the proposed system as the ability of an adaptive fouling control system to adjust backwash scheduling and chemical dosing so that achieving the target of purified water quality even during the fluctuation of raw water qualities.Subsequently, the water treatment system can achieve the capability for optimal total water cost operations under a target permeate flow rate and the percent of the recovery.Significantly, the data analytics in the CPCC reflect current operational requirements of water under local climate conditions, likewise contribute to the practical solution for sustainable water resource planning in the energy production.
Keywords: Water-Energy-Food Nexus Studies